Improving sexual and reproductive health knowledge and practice in Mozambican families with media campaign and volunteer family health champions - Paulo Henrique Pires; Ronald Siemens; Martins Mupueleque (Family Medicine and Community Health, 2019)
Objective To increase knowledge, attitudes and practice of sexual and reproductive health and family planning and to reduce maternal and neonatal mortality rates in Mozambique.Design An implementation research project’s intermediate evaluation, applying two cross-sectional surveys. The surveys were planned for 316 subjects before and after interventions.Setting Research performed in Natikiri district of Nampula province in northern Mozambique, targeting a suburban and rural populations in their homes.Participants 452 people were surveyed (91 before, 361 after), all belonging to the Macua ethnic group.Interventions A media campaign (2 weekly radio spots, bimonthly theatre performances) was performed for 8 months (2017 to 2018) and family health champions’ teachings (monthly home visits) performed for 3 months, on sexual and reproductive health and family planning. Outcome measures planned and measured were adolescent’s and adult’s knowledge, attitudes and practice about those. Data were analysed by gender, age group and frequencies, using a CI of 95% (p<0.5 statistically significant).Results Radio spots, community theatre and volunteer champions increased population’s knowledge about sexual and reproductive health and led to a more positive attitude toward family planning. Concerning attitude, results show differences between adults’ proportions before and after: (1) did you hear about sexual and reproductive health (p=0.0425); (2) knows project key messages (p<0.001); (3) knows prenatal visits importance (p=0.0301); (4) access to contraceptives was easy (p<0.001). Adolescents showed statistically significant differences before and after: (1) knows project key messages (p<0.001); (2) access to contraceptives was easy (p=0.0361). Family planning practice did not increase in both groups.Conclusion A health education intervention, using a media campaign and local volunteers, is useful to promote mother and child health. There is an unmet need for family planning and the use of modern contraception is below desired practice, needing further research about cultural barriers. Communication for behaviour change activities will pursue and impact will be assessed to document family planning practice improvement.